Improved Understanding of Industrial Process Relationships Through Conditional Path Modelling With Process PLS - Offermans, Tim; Hendriks, Lynn; van Kollenburg, Geert H.; Szymańska, Ewa; Buydens, Lutgarde M. C.; Jansen, Jeroen J. (Frontiers in Analytical Science, 2021)
Understanding how different units of an industrial production plant are operationally related is key to improving production quality and sustainability. Data science has proven indispensable in obtaining such understanding from vast amounts of historical process data. Path modelling is a valuable statistical tool to obtain such information from historical production data. Investigating how relationships within a process are affected by multiple production conditions and their interactions can however provide an even deeper understanding of the plant's daily operation. We therefore propose conditional path modelling as an approach to obtain such improved understanding, demonstrated for a milk protein powder production plant. For this plant we studied how the relationships between different production units and steps are dependent on factors like production line, different seasons and product quality range. We show how the interaction of such factors can be quantified and interpreted in context of daily plant operation. This analysis revealed an augmented insight into the process that can be readily placed in the context of the plant's structure and behavior. Such insights can be vital to identify and improve upon shortcomings in current plant-wide monitoring and control routines.